Analysis of the adhesion wear mechanism and brittle failure of carbide tools when dry machining the aeronautical titanium alloy: Ti-6Al-4V. (18th July 2008) - Nouari, Mohammed; Ginting, Armansyah
Titanium alloys are widely used for applications requiring high strength at elevated temperature and high mechanical resistance. The main problems encountered when machining this kind of materials are the low material removal rate and premature tool wear. In the current study, the usual titanium alloy Ti-6Al-4V is machined under orthogonal cutting configuration without using lubrication (dry machining). Three rake angles of 0°, 15° and 30°, three cutting speeds of 15, 30 and 60 m/min, and three feeds of 0.1, 0.2, and 0.3 mm were selected. The chip load (V.f) is used to calculate the flow localisation parameter β. The later is a good indication on the chip shape. It has been found that the serrated chip shape starts at β of 4.70 which corresponds to chip load V.f of 0.0045 m²/min. In this case, a brittle failure is produced by the formation of Built-Up-Layers (adhesion wear) at the tool-chip interface.